Adherencia al tratamiento y apoyo familiar en comerciantes hipertensos que laboran en el mercado Mayorista - Benítez Guzmán, Bryan Alberto (2023)
High blood pressure is characterized by being a chronic disease considered the main risk factor for suffering from cardiovascular diseases, which represent the main cause of death in Ecuador. This requires personalized control, since one of the fundamental pillars for treatment is Therapeutic adherence based on knowledge of the disease and family support, constituting a determinant to maintain an adequate quality of life in the patient. For this reason, a quantitative, descriptive, crosssectional research was proposed whose objectives were: Sociodemographically characterize the market merchants, Identify the level of therapeutic adherence, knowledge of the disease, family support and establish the relationship between family support and adherence to the treatment that merchants who suffer from high blood pressure have, 100 merchants participated in this research. Obtaining as results that 44% of the market's successful bidders are over 66 years old and 34% are between 56 and 65 years old; 69% are female, 48% are married and 28% are widowed, 85% have only completed primary school. 83% showed adherence to treatment, 51% have adequate knowledge about their disease and 64% receive support from their families. It was shown that there is no statistical relationship between family support and adherence to treatment. In conclusion, adequate education of the patient about their disease and including their family is essential to maintain adequate treatment and prevent complications